2010
DOI: 10.1002/hed.21544
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year follow‐up of oral functioning and quality of life in patients with oral cancer with implant‐retained mandibular overdentures

Abstract: Oral function and denture satisfaction were high and did not change over time for survivors. Deterioration in overall global health and QOL was associated with concurrent comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
2
26
1
1
Order By: Relevance
“…Patients with total laryngectomy had higher pain scores than partial laryngectomised patients or patients receiving other types of treatment in three studies [66,88,89]. Two studies reported that the combination of surgery and radiotherapy led to more pain in patients when compared to patients treated with surgery or radiotherapy only [62,90]. Other studies described more pain among patients who were treated with chemoradiotherapy when compared to patients who had undergone other treatment methods [54,82].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with total laryngectomy had higher pain scores than partial laryngectomised patients or patients receiving other types of treatment in three studies [66,88,89]. Two studies reported that the combination of surgery and radiotherapy led to more pain in patients when compared to patients treated with surgery or radiotherapy only [62,90]. Other studies described more pain among patients who were treated with chemoradiotherapy when compared to patients who had undergone other treatment methods [54,82].…”
Section: Resultsmentioning
confidence: 99%
“…The effect of implant‐prosthetic treatment on QoL and oral functions is assumed to be larger in non‐irradiated cancer patients than in irradiated cancer patients, as it was revealed that the scores of items related to the oral sequelae of radiotherapy did not improve after oral rehabilitation. However, QoL at 5‐year follow up showed no significant differences between irradiated and non‐irradiated patients, but it deteriorated between 1 and 5 years after placement of implant‐retained prosthesis due to concurrent comorbidity …”
Section: Discussionmentioning
confidence: 94%
“…Considering the oral effects stemming from radiotherapy and chemotherapy, the physiology of mastication may be directly affected, leading to eating and nutritional disorders and further affecting also taste perception and quality of life of cancer patients . In a recent prospective study, it was demonstrated that oral function 1 year after surgery in patients treated for malignancies in the tongue and/or floor of mouth had significantly deteriorated masticatory performance, bite force and dental state .…”
Section: Introductionmentioning
confidence: 99%